H-shaped liquid crystals inducing nematic order in the isotropic liquid. Issue 12 (26th September 2019) - Sayama, Shoumi; Muraki, Ryosuke; Yoshizawa, Atsushi
ABSTRACT: We prepared a homologous series of H-shaped liquid crystals I- n and investigated their phase transition properties using optical microscopy and differential scanning calorimetry. All the compounds exhibited a nematic phase at room temperature. The phase transition behaviour is explained in terms of molecular shape anisotropy. Furthermore, those compounds were found to exhibit electro-optical switching in the isotropic liquid in the vicinity of the nematic–isotropic liquid transition, indicating that the microscopic nematic order with a certain coherence length of the molecules exists in the optically isotropic temperature range. GRAPHICAL ABSTRACT: